2017
DOI: 10.1126/sciadv.1700307
|View full text |Cite
|
Sign up to set email alerts
|

Above 400-K robust perpendicular ferromagnetic phase in a topological insulator

Abstract: Topological surface states reveal proximity-induced ferromagnetism with perpendicular anisotropy persisting above 400 K.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
160
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(172 citation statements)
references
References 35 publications
8
160
2
2
Order By: Relevance
“…The optimized films had the room-temperature saturation magnetization (M s ) of 99 emu/cm 3 (RT bulk value: 110 emu/cm 3 ) with an H c of 2.4 Oe, which was the lowest value ever reported for TmIG films. [7][8][9][10]12 TmIG films with low coercive field require low current induced effective field to switch the magnetization so that the current density of magnetization switching can be reduced. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The optimized films had the room-temperature saturation magnetization (M s ) of 99 emu/cm 3 (RT bulk value: 110 emu/cm 3 ) with an H c of 2.4 Oe, which was the lowest value ever reported for TmIG films. [7][8][9][10]12 TmIG films with low coercive field require low current induced effective field to switch the magnetization so that the current density of magnetization switching can be reduced. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7,8 The PMA was originated from magnetization-lattice coupling under sufficient tensile strain, and overcomes the shape anisotropy, owing to the large magnetostriction constant of TmIG. Anomalous Hall effect was observed in TI/TmIG heterostructure up to a temperature as high as 400K, 9 making TI/TmIG a very promising candidate for realization of QAHE at elevated temperature. Moreover, a current-induced magnetization switching has been demonstrated in Pt/TmIG heterostructure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that TmIG films had been grown mostly by pulsed laser deposition (PLD) 79,11,12 . However, the small deposition area is the major shortcoming of PLD, limiting its application in industry.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the closely matched lattice structures, crystalline (S)GGG is widely used as the growth substrate for a general class of iron garnets described by X 3 Fe 5 O 12 (XIG) [16,17] with spintronic applications, such as TIG [18][19][20][21][22], YIG [23][24][25][26][27][28][29][30][31][32][33][34][35], BIG [36][37][38], HIG [39], TbIG [40] and GdIG [41] (X = Tm, Yb, Bi, Ho, Tb and Gd, respectively). The epitaxial strain induced by the (S)GGG substrate, tunable by the B-site substitution, can be used to effectively manipulate the magnetization and magnetic easy-axis of the XIG films.…”
Section: Introductionmentioning
confidence: 99%